A Strategy to Improve the Learning of Political Culture with Debate Method in Vocational High School 1 Bekasi - Utomo, Kurniawan Prambudi; Kamal, Fahmi (Universitas Terbuka, 2020)
This research was conducted to form one part of national education and improve the culture of literacy among vocational students who are effective and efficient as well as to train intelligence and the ability to manage emotionally elegant so that it is expected to prepare future leaders. The purpose of this research is to examine the variables of political culture material with the method while the methodology of this research is Classroom Action Research (CAR) or Classroom Action Research. This class action research is a form of self-reflection carried out by researchers that are seen in the situation under study aimed at improving the quality of learning, as well as to improve the performance of the education system using a qualitative approach, the time of the implementation of this study was carried out for three months, namely inÃ‚Â June - September 2017 and the results of the study concluded that in the early stages of the cycle the increase in student understanding reached 62.5% and considered sufficient to understand while the research in the final cycle, after the given direction, and ability, students showed the role of some students quite significant, reaching 22.5% of students so that the understanding of political culture debate reached 100%.